How Much Does Economic Crisis Affect Sustainability Transitions? A Social Network Analysis of the Italian Biofuel Sector - Falcone, Pasquale Marcello; Sica, Edgardo (Economy of Regions, 2015)
The present paper investigates the impact of he current economic crisis on the process of sustainability transitions by exploring the case of a green niche, namely the biofuel sector. From a methodological point of view, we employ a social network analysis aimed at comparing the Italian biofuel niche in two different time periods, specifically before and during the crisis. Our findings provide evidence that biofuel actors are responding to the economic crisis by raising the degree of their knowledge exchange. At the same time, they are exhibiting a general scepticism about the future development of the niche, showing a lower level of expectations compared to that of 2007 (i.e. before the crisis). These results suggest that the economic crisis is concretely hindering the transition towards a biofuel-based regime by affecting the degree of maturity of the niche.